Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1002/jms.3371
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-deuterium exchange of α-carbon protons and fragmentation pathways in N-methylated glycine and alanine-containing peptides derivatized by quaternary ammonium salts

Abstract: Recently, we developed a selective and efficient method of hydrogen-deuterium exchange (HDX) at the α-carbon (α-C) of sarcosine residue (N-methylglycine) in model peptides [Bąchor et al. J. Mass Spectrom. 2014, 49, 43]. Here, we report the influence of quaternary ammonium (QA) group on HDX at the α-C of sarcosine and N-methylalanine in peptides. The obtained results suggest a significant acceleration of the HDX in sarcosine residue caused by the presence of QA. The effect depends on the distance between the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 19 publications
(34 reference statements)
2
15
0
Order By: Relevance
“…Additionally, we observed that in the case of the α ‐C hydrogens of the N,N,N ‐trialkylglycine (betaine) residue in peptides, described by us previously , the H/D exchange occurs within 1 min, which suggests the effect of the quaternary ammonium group on the acidity of the α ‐C hydrogens . We have also found the possibility of such HDX at the α ‐C of the N ‐methyl alanine residue in peptides derivatized by a quaternary ammonium group .…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…Additionally, we observed that in the case of the α ‐C hydrogens of the N,N,N ‐trialkylglycine (betaine) residue in peptides, described by us previously , the H/D exchange occurs within 1 min, which suggests the effect of the quaternary ammonium group on the acidity of the α ‐C hydrogens . We have also found the possibility of such HDX at the α ‐C of the N ‐methyl alanine residue in peptides derivatized by a quaternary ammonium group .…”
Section: Introductionsupporting
confidence: 71%
“…Such a procedure allowed one to observe the presence of deuterons introduced at the α ‐C. Based on our previous research , the α ‐C deuterons of N ‐methyl glycine and N ‐methyl alanine residues do not undergo the back exchange at acidic conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Such results may suggest the different fragmentation mechanism during ESI‐MS/MS analysis of QCP conjugates. The fragmentation pathways observed for QCP may include the tertiary amine elimination according to the Hofmann elimination . This observation opens the possibility of application of the ions corresponding to the protonated cryptand amine as a reporter group during the tandem mass spectrometry analysis, especially multiple reaction monitoring.…”
Section: Resultsmentioning
confidence: 93%
“…This resulted in a neutral ketene structure at the Nfragment and a y-type ion at the C-fragment. Their studies on deuterated QA-tagged oligosarcosine further showed that formation of y-ions involved the migration of a proton from the α-C-H bond of sarcosine residue [56]. For peptoids, the oxazolone B-ion is a quaternary ammonium cation.…”
Section: Fragmentation Mechanism: Y-ion Formationmentioning
confidence: 99%
“…This study suggested that the presence of the acidic N-H a bond was crucial for the formation of peptide-y-ions. Recently, Szewczuk and coworkers carried out a series of studies on the fragmentation pathways in N-substituted oligopeptides, including oligoproline and oligosarcosine, with a quaternary ammonium (QA) group tagged at the N-terminus [56,57]. These peptides did not contain backbone N-H groups.…”
Section: Fragmentation Mechanism: Y-ion Formationmentioning
confidence: 99%